Sensate Reverse Medial Plantar Flap for Reliable Forefoot Reconstruction with Flow-through Anterolateral Thigh Flap - Masami Murakami, MD; Keijiro Hori, MD, PhD; Yosuke Niimi, MD, PhD; Yoji Nagashima, MD, PhD; Hiroyuki Sakurai, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. A reverse medial plantar flap is a major option for reconstructing the plantar forefoot. However, reconstruction of the distal forefoot stretches the vessels, causing tightness, and the skin graft to the donor site adds pressure to the vessel, precipitating venous congestion. We used a reverse medial plantar flap to reconstruct the lateral distal forefoot with a flow-through of the anterolateral thigh (ALT) flap for donor site coverage to maintain physiological and stable blood flow. A 74-year-old woman presented to our hospital with a 20-year history of left forefoot skin tumor. The tumor was resected, and histological examination revealed porocarcinoma in the cystic poroid hidradenoma. Additional excision was performed, and the defect area was covered with a biodegradable artificial dermis. The skin defect of the lateral distal plantar area was reconstructed with a reverse medial plantar flap with a reverse flow Y-V pedicle extension method, and the donor site was reconstructed with an ALT flap interposing the lateral circumflex femoral artery with the transected posterior tibial artery. The flap was completely engrafted without any complications, including arterial ischemia or venous congestion, during or after surgery. A distally based reverse medial plantar flap with a reverse flow Y-V pedicle extension method and flow-through of the ALT flap should be considered for the reconstruction of the lateral distal forefoot with a large defect. This method can maximize flap extension and maintain stable arterial inflow and venous drainage without the major complications of venous congestion.